Komunikasi Persuasif Program Dakwah FDKI Mengaji IAIN Syaikh Abdurrahman Siddik Bangka Belitung - Azfa, Pani; Gustin, Gustin; Musa, Musa (KOMUNIKASIA: Journal of Islamic Communication and Broadcasting, 2025)
A preacher must be able to understand society because it often consists of diverse backgrounds and beliefs, and should strive to build dialogue that respects differences and upholds the values of tolerance. Religious activities also support community-based religious practices such as Qur’an recitations, sermons, or religious study groups. This helps strengthen religious communities both in social and academic environments. This research focuses on the research question: how is persuasive communication implemented in the FDKI Mengaji da'wah program at IAIN Syaikh Abdurrahman Siddik Bangka Belitung? The findings conclude that persuasive communication in the FDKI Mengaji da'wah program at IAIN Syaikh Abdurrahman Siddik Bangka Belitung is carried out by maintaining proper attitude as a preacher and by becoming uswatun hasanah (a good role model). The FDKI Mengaji program includes activities such as Qur’an recitation, prayers, literacy, congregational prayers, and commemoration of religious holidays. Through persuasive communication, FDKI Mengaji also upholds local traditions in Bangka, particularly the practice of nganggung.